The Analysis of Effect Size of the PBL Model on Science Competence of High School Students - Media Roza; Festiyed Festiyed; Asrizal Asrizal; Desnita Desnita (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2022)
This study aimed to describe a problem-based learning model (PBL) that had succeeded in increasing the competence of high school students. The research method used meta-analysis. The research process included determining research topics, determining data selection criteria, searching for literature, grouping data information, interpreting data, and drawing conclusions. The database was articles published in Scopus-indexed journals and accredited by SINTA. The articles analyzed were articles published in the last 5 years, namely in 2017-2021. 25 articles met the criteria for further analysis. The data analysis technique used an effect size. Effect size values were measured and grouped by subject, grade level, and type of student competency. The results showed that based on the type of science subjects, the PBL model was more widely applied to physics and chemistry subjects compared to biology subjects. The effect size results fell into the medium to very high category. Based on grade level, PBL was effectively used for class XI with high criteria. From this research, it was also known that the critical thinking, problem-solving, and cognitive aspects of students had a high effect size by applying the PBL model. Therefore, the PBL model was effectively applied in science learning in high schools.